Condition-dependent responses of fish to motorboats. (25th November 2020) - Harding, H. R.; Gordon, T. A. C.; Wong, K.; McCormick, M. I.; Simpson, S. D.; Radford, A. N.
Abstract : Anthropogenic noise is a pollutant of global concern that has been shown to have a wide range of detrimental effects on multiple taxa. However, most noise studies to-date consider only overall population means, ignoring the potential for intraspecific variation in responses. Here, we used field experiments on Australia's Great Barrier Reef to assess condition-dependent responses of blue-green damselfish ( Chromis viridis ) to real motorboats. Despite finding no effect of motorboats on a physiological measure (opercular beat rate; OBR), we found a condition-dependent effect on anti-predator behaviour. In ambient conditions, startle responses to a looming stimulus were equivalent for relatively poor- and good-condition fish, but when motorboats were passing, poorer-condition fish startled at significantly shorter distances to the looming stimulus than better-condition fish. This greater susceptibility to motorboats in poorer-condition fish may be the result of generally more elevated stress levels, as poorer-condition fish had a higher pre-testing OBR than those in better condition. Considering intraspecific variation in responses is important to avoid misrepresenting potential effects of anthropogenic noise and to ensure the best management and mitigation of this pervasive pollutant.